2013
DOI: 10.1002/ejoc.201300230
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of 2,5‐Bis(dodecanoxy)phenyleneethynylene‐Butadiynes by Sonogashira Coupling Reaction

Abstract: The synthesis of a 2,5‐bis(dodecanoxy)phenyleneethynylene‐butadiyne series with 2, 4, 6 and 8 phenyl rings is reported. Sonogashira coupling reaction, rather than the Glaser/Eglinton/Hay reactions classically used for butadiyne formation was applied. The molecular structures of all compounds were confirmed by 1H, DEPT‐135, APT 13C, MALDI‐TOF, FTIR and FT‐Raman analyses. The linear and nonlinear optical properties were studied in solution by UV/Vis, static and time‐resolved fluorescence, and by two‐photon absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Marder and co-workers 173 extended their studies on organic diynes in which the thienyl ring was inserted into the center and end-capped with substituted phenyl and pentafluorophenyl rings (114, 115, Chart 3). Contrary to the phenylene system, both electron-donating and -withdrawing parasubstituents on the terminal phenyl rings (114) shifted the λ max abs and λ max em to lower energies. The shift was more pronounced with electron acceptor groups than with electron donors.…”
Section: Organic Di- Oligo- and Poly-ynesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marder and co-workers 173 extended their studies on organic diynes in which the thienyl ring was inserted into the center and end-capped with substituted phenyl and pentafluorophenyl rings (114, 115, Chart 3). Contrary to the phenylene system, both electron-donating and -withdrawing parasubstituents on the terminal phenyl rings (114) shifted the λ max abs and λ max em to lower energies. The shift was more pronounced with electron acceptor groups than with electron donors.…”
Section: Organic Di- Oligo- and Poly-ynesmentioning
confidence: 99%
“…In a recent study, a similar type of methodology has been adopted to synthesize 2,5-bis­(alkoxy)­phenylene ethynylene oligo- and polymers. , For the synthesis of oligo­(1,4-phenylene ethynylenes) ( n = 16), Schumm and Tour reported IDC methodology using Merrifield’s resin. Huang and Tour using the same method successfully synthesized a 120 Å long 17-mer of oligo­(1,4-phenylene ethynylenes).…”
Section: Synthesismentioning
confidence: 99%
“…1:2:3 is indicative of a lamellar system and representative of a smectic phase with a corresponding layer spacing d of 3.48 nm. In this respect, the theoretical distance of its more extended conformation determined from the equilibrium geometries through density functional theory was of 3.68 ± 0.0086 nm, 17 suggesting that the alkyl chains are tilted 19°with respect to the normal and, thus, a signature of a tilted smectic phase, such as illustrated in the model in Figure 4 for 6DAc and mentioned in Table 1. It is worth noting that, at higher angles, two sets of broad bands coexist with the well-defined intense peaks.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Within this context, we present a supramolecular order study of a 2,5-bis(dodecanoxy)phenyleneethynylene−butadiyne series of oligomers in the solid state (Figure 1), whose syntheses and spectroscopic and photophysical properties were reported elsewhere. 17 These rod-like macromolecules by themselves resemble bricks, and low dichroic rates around 0.2 of 1.0 are obtained by rubbing thin films. We found that indeed the series exhibits wide-ranging mesophases, which are dependent upon the length of the oligomer.…”
Section: ■ Introductionmentioning
confidence: 99%